SOLUTION
Given the question in the image, the following are the solution steps to answer the question.
STEP 1: Write the given data values
![\begin{gathered} foci\Rightarrow(1,4-√(45)),(1,4+4+√(5)) \\ asymptotes\Rightarrow y=2x+2,y=-2x+6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zoou5inte3ottmk47ij15ak91lsrppe4ng.png)
STEP 2: Write the equation
The equation of a hyperbola is given as:
![((y-k)^2)/(b^2)-((x-h)^2)/(a^2)=1](https://img.qammunity.org/2023/formulas/mathematics/college/2chf3744yur4psmq1mt5gahrceonr2yag1.png)
where (h,k) is the center, a and b are the lengths of the semi-major and the semi-minor axes.
STEP 3: Explain the given data
![\begin{gathered} h=1,(k-4+3√(5))^2=a^2+b^2, \\ (k-3√(5)-4)^2=a^2+b^2 \\ (b)/(a)=2 \\ -2h+k=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d7slgcn3nkxj0a3zafv1zjpxw9aoct4fos.png)
STEP 4: Find the values of h,k,a and b
![\begin{gathered} h=1 \\ From: \\ -2h+k=2 \\ -2(1)+k=2 \\ -2+k=2 \\ k=2+2=4 \\ k=4 \\ \\ \text{To get b and a,} \\ (b)/(a)=2 \\ By\text{ calculation,} \\ a=3,b=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rl9buhhsp6ob6xcnfn5vgrxqdpiwx8vubj.png)
STEP 5: Get the equation of the hyperbola
![\begin{gathered} By\text{ substitution into the formula in step 1,} \\ ((y-4)^2)/(6^2)=((x-1)^2)/(3^2)=1 \\ Vertex\text{ form}\Rightarrow((y-4)^2)/(36)-((x-1)^2)/(9)=1 \\ General\text{ form will be}\Rightarrow4x^2-8x-y^2+8y+24=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/oohohzg3mdagchzsx0wazf9d9wxnkhebru.png)
Hence, the equation of the hyperbola will be:
General form:
![\begin{equation*} 4x^2-8x-y^2+8y+24=0 \end{equation*}](https://img.qammunity.org/2023/formulas/mathematics/college/7ztss7ynoltgkn22plv60ptj10r7p3df5p.png)
The vertex form is given as:
![\begin{equation*} ((y-4)^2)/(36)-((x-1)^2)/(9)=1 \end{equation*}](https://img.qammunity.org/2023/formulas/mathematics/college/fqf33vguigwr7gwp7i2d7412jph4i1q412.png)